Effects of different forms and origins of oilseeds on dynamics of ruminal biohydrogenation of long‐chain fatty acids in vitro. Issue 6 (26th March 2015) - Hoffmann, A.; Steingass, H.; Schollenberger, M.; Terry, H.; Hartung, K.; Weiss, E.; Mosenthin, R.
Summary: Dietary unsaturated fatty acids (FA) are intensively hydrogenated in the rumen, resulting in reduced amount of poly‐unsaturated fatty acids (PUFA) and accumulation of several biohydrogenation (BH) products. In this study, BH of PUFA originating from different oilseeds (linseed, soya beans, sunflower seed and rapeseed) present in crushed oilseeds or their free oils were assessed in vitro . The assay substrates were incubated in buffered rumen fluid for 0, 6, 12 and 24 h. After incubation, the FA pattern of the incubated samples was analysed using gas chromatography. Biohydrogenation is defined as disappearance of double bonds (DB) calculated from the contents of unsaturated FA. After 24‐h incubation, the DB contents of all oilseeds were reduced (p < 0.001) by 40–60%. The reduction was higher (p < 0.001) for the crushed form compared with the oil form. In addition, linseed and sunflower seed known as oilseeds with high contents of linolenic acid C18:3 c9, 12, 15 (LNA) and linoleic acid C18:2 c9, 12 (LA), respectively, showed a higher (p < 0.001) accumulation of the BH intermediates conjugated linoleic acid (CLA, isomer C18:2 c9t11) and vaccenic acid (C18:1 t11) for the crushed form, when compared with the oil. These results suggest an inherent effect of the physical form of the assay oilseeds on in vitro BH. Changes in FA pattern during BH in vitro can be attributed to both source and physical form of the assay oilseeds. However, further investigations are warranted to ensure whether the observed in vitro effects on ruminal BH can be confirmed in vivo .